The Impact of Work Engagement on Workforce Agility with Psychological Empowerment as A Moderator - Hanifah, Reinanda Isfania; Wicaksana, Seta A. (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: The objective of this study is to investigate the impact of work engagement and psychological empowerment as moderator variables on workforce agility in the State Civil Apparatus of organisation X. Design/methodology/approach: This study is quantitative and uses the Moderation Regression Analysis (MRA) technique with the SPSS 23 application. The measuring instruments used are the Workforce Agility Scale (Sherehiy, 2008) to measure workforce agility, the Psychological Empowerment Scale (Spreitzer, 1995) to measure psychological empowerment, and the UWES-17 (Schaufeli & Bakker, 2004) to measure work engagement. Findings: The findings of the study reveal a significant positive relationship between work engagement and workforce agility. Psychological empowerment can have a positive effect on the regression value as a moderator. Research limitations/implications: To enhance and optimize research results, additional methods are required to obtain in-depth information. Future research should conduct interviews with relevant parties to ensure and strengthen the phenomenon under study. Paper type: Research paper